Isoflavones and Fatty Acids from Crotalaria aegyptiacea - Elgindi, M.R.; Mahmoud, I.I.; Attia, H.G. (Asian Journal of Chemistry, 2010)
The methanolic extract of Crotalaria aegyptiaca was concentrated and then extracted with chloroform. The ethyl acetate extract from chloroform residue was subjected to chromatographic techniques that revealed the presence of genistein, genistin and 5,7,4′-trihydroxy-6,8-diprenyl isoflavone. The fatty acids detected are capric acid, lauric acid, arachedic acid and myrisitic acid. The major hydrocarbon was proved to be squalene (36.24 %), while the major sterol was cholesterol (3.20 %).